Seizure in emergency department: Finding the Zebra among the Horses (Indian Journal of Case Reports, 2022)
Aortic dissection is a life threatening emergency that mandates early and precise diagnosis. Chest pain is the most common presenting complaint and it is classically described as sharp excruciating and having tearing or ripping quality with location migrating as the dissection extends along the aorta. The frequency of neurological involvement is reported as between 17-40 %. Seizure as exclusive manifestation of aortic dissection is very uncommon and only two such cases have been reported till date in literature. We report a case of type A aortic dissection who presented with seizures to our Emergency Department (ED).